Recognising Handwritten Multi-digit Data using Convolutional Neural Networks - Shamim; P. Ravindra (The Bioscan, 2024)
Digitization is seen as an essential part these days. Many vendors at neighborhood markets still use paper bills, so this may be helpful there. In response to this urgent issue, this study introduces a fresh method for digitizing handwritten invoices. To replace handwritten invoices with digital ones, the proposed method employs image processing and neural networks. The proposed method is hassle-free for the vendor as all he has to do is snap a photo of the handwritten invoice.